The Modern Problem-Solving Court Movement: Domination of Discourse and Untold Stories of Criminal Justice Reform - Mae C. Quinn (Washington University Journal of Law & Policy, 2009)
This Article examines modern criminal justice reforms. It focuses on the claims of the contemporary problem-solving court movement—a movement that has resulted in the development of thousands of specialized criminal courts across the country over the last two decades.
Keywords: Judicial reform; Criminal justice administration; Criminal justice reform; Courts of special jurisdiction; Judicial experiments